Review of ecological perspectives on climate change in Nigeria Review of ecological perspectives on climate change in Nigeria (2014)
A review has been carried out on the ecological perspectives on climate change in Nigeria. The country is one of the leading producers of crude oil and a major contributor of greenhouse gases that cause climate change. The current and future consequences of climate change have been discussed with local examples of ecological effects. Efforts to control climate change are highlighted at local and global scales since the effects are not restricted within national boundaries. It is recommended that greenhouse gas emissions should be reduced through efficient energy use, diversification of energy sources away from fossil fuels and safe agricultural practises